Antibiotic Sensitivity in Pseudomonas aeruginosa of Diabetic Patient's Foot Ulcer - Pratiwi Apridamayanti; Khairunnisa Azani Meilinasary; Rafika Sari (Universitas Indonesia, 2016)
Diabetes Mellitus (DM) patients are at risk to have the diabetic ulcer. The main reason for DM's patient with ulcer complication to be treated and healed in hospital is bacterial infection. One of many bacteria that infects diabetic ulcer is Pseudomonas aeruginosa. This conditian can be treated by antibiotic. The using antibiotic is often inaccurate causing the microbe resistance. To choose the right antibiotic, it needs to test the antibiotic's sensitivity towards Pseudomonas aeruginosa. The aimed of this study was to determine the sensitivity of antibiotics against Pseudomonas aeruginosa. Sample was taken from diabetic ulcers swab with grade III and IV Wagner. The identification of bacteria was managed using the biochemical test and Gram staining test. Antibiotic sensitivity was determined by Kirby Bauer method. Antibiotics that were found still sensitive towards Pseudomonas aeruginosa included ciprofloxacin, norfloxacin, imipenem, levofloxacin, meropenem, ceftriaxone, and cefotaxime, whereas cefadroxil and amikacin were resistant. Antibiotics that can be used for Pseudomonas aeruginosa in diabetic foot ulcer patients are ciprofloxacin, norfloxacin, imipenem, levofloxacin, meropenem, ceftriaxone, and cefotaxime.